Military expenditure and economic growth empirical evidence from Malaysia - Nur Surayya Mohd Saudi; Ariffin Ismail; Rogis Baker; Saizal Pinjaman; Aida Nasirah Abdullah; Nurhana Mohamad Rafiuddin; Amiruddin Sulaiman (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The relationship between military expenditure and economic growth has attract ample interest among economists as well as policy makers. The importance of expanding defence expenditure is substantially to coincide with national security and defence. The purpose of this study is to explore the impact of military expenditure on economic growth in Malaysia. An econometrics time series analysis is employed using ARDL estimates spanning from the year 1979 to 2017. The empirical findings reveal a negative relationship between military expenditure and Gross Domestic Products (GDP). Despite the inverse relationship between defence expenditure and economic growth, Malaysia should not neglect the investment on efficient military expenditure, as it has proven that in some countries, defence expenditure promotes a long run economic growth by promoting more job opportunities, protecting the nation and thus, achieving sustainable development. It is recommended to add more variables in future study that can relate security and defence for the country like numbers of crime, and numbers of migrants and refugees. Conclusively defence and security are the important factors for the country in generating the world and public’s confidence and to captivate foreign direct investment. Hence, adequate policy making on military expenditure are utmost important to promote economic growth.